Migration behavior of gaseous ruthenium tetroxide under boiling and drying accident condition in reprocessing plant. Issue 6 (3rd June 2018) - Yoshida, Naoki; Ohno, Takuya; Amano, Yuki; Abe, Hitoshi
ABSTRACT: In the boiling and drying accident of high-level liquid waste in the fuel reprocessing plant, behavior of ruthenium (Ru) has attracted much attention because Ru could form volatile compounds such as ruthenium tetroxide (RuO4 ) and could be released into the environment. To contribute towards safety evaluation of this accident, the migration behavior and the leak path factor of the gaseous ruthenium compound has been experimentally measured in this study. The experiment was proceeded by using the 'Ruthenium Migration Evaluating Apparatus, ' which partially simulates the atmospheric condition (temperature, flow rate, and composition of water vapor and gaseous nitric acid mixture) of migration pathway in the accident. Experiments with dry air and water vapor were also performed as the control experiment to discuss the effect of nitric acid. As a result, the experiment with dry air and the experiment with water vapor demonstrated that the majority of the ruthenium deposited along the migration pathway. On the other hand, the experiment with the water vapor containing gaseous nitric acid demonstrated that almost all of the ruthenium passed through the migration pathway without deposition. These results suggested that the migration behavior of gaseous ruthenium will be affected by the gas-phase composition.